Ferramentas de Autoria para Aplicações na TV Digital Voltadas a Produtores de Conteúdo: Uma Revisão Sistemática de Literatura - Sousa, Li-Chang Shuen; Moreno, Marcelo Ferreira; Soares Neto, Carlos de Salles (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2025: Proceedings of the 31st Brazilian Symposium on Multimedia and the WebDO - 10.5753/webmedia.2025.16103, 2025)
This systematic literature review aims to identify the main functional and non-functional requirements for the development of authoring tools for interactive digital TV content, targeting nonprogrammer content producers, in the context of the transition from channel-oriented TV to the application-oriented platform of TV 3.0. Based on a search across seven academic databases, 1,642 studies published between 2007 and 2025 were retrieved. After screening and applying inclusion criteria, 106 studies were selected, and 21 met the quality threshold for final review. Findings indicate that most proposed tools are designed for programmers or users familiar with programming languages such as NCL/NCLua, with only one solution explicitly targeting non-programmer content producers. Common functional requirements include visual editing interfaces, reusable templates, multimodal interaction configuration, application preview, automatic validation, and export to NCL/NCLua compatible with the Ginga middleware. Non-functional requirements emphasize usability for non-programmers, adherence to SBTVD standards, modularity, and cross-platform portability. However, significant gaps remain, particularly the lack of tools integrated into early editorial workflows and the limited support for collaborative authorship and content management systems.